Glucagon-Like Peptide-1 Is Associated With Systemic Inflammation in Pediatric Patients Treated With Hematopoietic Stem Cell Transplantation - Ebbesen, Maria; Kissow, Hannelouise; Hartmann, Bolette; Kielsen, Katrine; Sørensen, Kaspar; Stinson, Sara Elizabeth; Frithioff-Bøjsøe, Christine; Esmann Fonvig, Cilius; Holm, Jens-Christian; Hansen, Torben; Holst, Jens Juul; Müller, Klaus Gottlob (Frontiers in Immunology, 2021)
Patients undergoing allogeneic hematopoietic stem cell transplantation (HSCT) are challenged with severe side effects, which are propagated by mucosal barrier disruption, and the related microbial translocation and systemic inflammation. Glucagon-like peptide-1 (GLP-1), a well-known incretin hormone, possesses anti-inflammatory properties and promotes regeneration of damaged intestinal epithelium in animal studies. We hypothesized that the immense inter-individual variation in the degree of mucosal damage and systemic inflammation, seen after HSCT is influenced by endogenous GLP-1. In this prospective study we measured serial weekly fasting plasma GLP-1, along with C-reactive protein (CRP), and citrulline in 82 pediatric patients during allogeneic HSCT together with a fasting plasma GLP-1 in sex- and age-matched healthy controls. Overall, GLP-1 levels were increased in the patients during the course of HSCT compared with the controls, but tended to decrease post-transplant, most pronounced in patients receiving high-intensity conditioning regimen. The increase in CRP seen in the early post-transplant phase was significantly lower from day +8 to +13 in patients with GLP-1 above the upper quartile (>10 pmol/L) at day 0 (all P ≤ 0.03). Similar findings were seen for peak CRP levels after adjusting for type of conditioning (-47.0%; 95% CI, -8.1 – -69.4%, P = 0.02). Citrulline declined significantly following the transplantation illustrating a decrease in viable enterocytes, most evident in patients receiving high-intensity conditioning regimen. GLP-1 levels at day 0 associated with the recovery rate of citrulline from day 0 to +21 (34 percentage points (pp)/GLP-1 doubling; 95% CI, 10 – 58pp; P = 0. 008) and day 0 to day +90 (48 pp/GLP-1 doubling; 95% CI, 17 – 79pp; P = 0. 004), also after adjustment for type of conditioning. In conclusion, this study strongly suggests that GLP-1 influences regeneration of injured epithelial barriers and ameliorates inflammatory responses in the early post-transplant phase.